Middle manager capabilities and organisational performance: the mediating effect of organisational capacity for change - Sukoco, Badri Munir; Lestari, Yetty Dwi; Susanto, Ely; Nasution, Reza Ashari; Usman, Indrianawati (Emerald Group Holdings Ltd., 2022)
Purpose: This study aims to investigate the mechanism that transforms middle manager capabilities (MMCs) into organisational performance (OP). This study proposes that organisational capacity for change (OCC) might mediate the relationship between MMCs and OP. Design/methodology/approach: The proposed hypotheses were tested using data derived from a survey distributed to 89 heads of department of 34 subjects from the 11 top universities in Indonesia. Findings: The findings indicate that MMCs positively influence OCC and OP and that OCC positively influences the OP. Furthermore, the authors found that OCC mediates the positive effect of MMCs on OP. Originality/value: The authors empirically investigated the hypothesis that MMCs, in the context of higher education, play a crucial role in determining OCC and OP. Furthermore, the capacity of organisations to adapt to the changing environment mediates the capabilities of the middle managers in relation to OP. In addition, the authors empirically investigated OCC in three dimensions (learning, process and context) that were previously only proposed and discussed conceptually. © 2020, Emerald Publishing Limited.